Phillyrin restores metabolic disorders in mice fed with high-fat diet through inhibition of interleukin-6-mediated basal lipolysis - Fang, Zhizheng; Wei, Lu; Lv, Yanping; Wang, Tongsheng; Hamezah, Hamizah Shahirah; Han, Rongchun; Tong, Xiaohui (Frontiers in Nutrition, 2022)
The function of white adipose tissue as an energy reservoir is impaired in obesity, leading to lipid spillover and ectopic lipid deposition. Adipose tissue inflammation can reduce the efficacy of lipid storage in adipocytes by augmenting basal lipolysis through producing interleukin-6 (IL-6). Therefore, pharmacological compounds targeting adipose tissue inflammation or IL-6 signaling might have the potential to combat obesity. This study aims to investigate the impact of Phillyrin, which is frequently used for treating respiratory infections in clinics in China, on obesity-related metabolic dysfunctions. Firstly, a mouse model of diet-induced obesity is used to assess the pharmacological applications of Phillyrin on obesity in vivo. Secondly, ex vivo culture of adipose tissue explants is utilized to investigate actions of Phillyrin on IL-6-linked basal lipolysis. Thirdly, a mouse model of IL-6 injection into visceral adipose tissue is explored to confirm the anti-basal lipolytic effect of Phillyrin against IL-6 in vivo. The results show that Phillyrin treatment reduces circulating level of glycerol, decreases hepatic steatosis and improves insulin sensitivity in obese mice. Meanwhile, Phillyrin attenuates obesity-related inflammation and IL-6 production in adipose tissue in obese mice. Furthermore, Phillyrin treatment results in resistance to IL-6-induced basal lipolysis in adipose tissue through suppressing expression of adipose triglyceride lipase (ATGL) both in vivo and in vitro. Collectively, these findings suggest that Phillyrin can restrain lipid efflux from inflamed adipose tissue in obesity by inhibiting IL-6-initiated basal lipolysis and ATGL expression, and thus is a potential candidate in the treatment of obesity-associated complications.